Techno-Economic Analysis of Blue Methanol Production from Natural Gas with Carbon Capture in Indonesia - Samuel Pangeran Aletheia; Meyland Meyland (Sultan Publisher, 2024)
Methanol market in Indonesia is projected to grow with Compound Annual Growth Rate of 3.2% by 2034. Utilizing natural gas as a feedstock and employing carbon capture and storage technology using activated metildietanolamin with piperazine (MDEA-PZ), the process is designed to produce methanol with a low carbon footprint. The process design and simulation were carried out using Aspen HYSYS, focusing on mass and energy balances across pre-treatment, syngas formation, methanol synthesis, purification and carbon capture stages. The pilot-scale plant with a capacity of 100,000 tons per year located in the Special Economic Zone (KEK) Arun, Aceh, demonstrating promising results with an Internal Rate of Return (IRR) of 11.73%, a Net Present Value (NPV) of USD 166.63 and levelized cost of methanol (LCOM) of 611.61 /ton MeOH. Compared to other low emission chemical plant, this plant offers promising economic feasibility.